Homeless Clients' Circulation in Emergency Care: Rethinking Poverty Governance as Urban Impasse - Daniela Krüger (Tijdschrift voor economische en sociale geografie, 2024)
Studies concerned with how local states govern the urban poor have long focused on the state's attempts to control, criminalise and exclude individuals from public spaces. Researchers recently shifted this focus; they increasingly engage with organisations and front-line practices relating to care. Underlying these analyses is the question of how urban governance rubs off on front-line work and conditions for the urban poor. In their research, scholars rarely study through which organisational mechanisms front-line workers and clients encounter each other. This article addresses 112 calls issued for unhoused individuals by third parties in Urgencity, a city in Germany. It sheds light on institutional and everyday logics that regularly bring third parties, emergency care front-line workers and marginalised clients into contact. These calls often blur boundaries of illness and poverty and care and control and result in clients' circulation in emergency care: an urban impasse for front-line workers.
Keywords: 330; Poverty governance; urban impasse; homelessness; emergency care; third party calls